NUMERICAL SIMULATOR FOR NATURALLY FRACTURED RESERVOIRS USING PERMEABILITY TENSORS AND TIME DEPENDANT FACTORS (2009)
ABSTRACT Understanding the behavior of Naturally Fractured Reservoirs (NFR) has been one of the biggest challenges assumed by many researchers worldwide working in the field of reservoir characterization, modeling and simulation. Due to the high number of NFRs around the world and consequently the significant quantity of oil and gas contained within them, these reservoirs are a very attractive target for the oil industry. However, due to the degree of complexity involved in their modeling, they require a considerable investment of both time and money. Construction of a numerical simulation tool that implements two more recent technological concepts namely tensor permeability and time dependant form factors have a great impact when modeling more realistically the NFR performance. SIMYNF is able to characterize permeability in the three dimensions of the fractured system and the inter-porous flow present in matrix-fracture systems; based on finite differences for black oil reservoir with double porosity and/or double permeability, three phases, three dimensions, Darcy’s flow and isothermic conditions. It is capable of modeling vertical, horizontal and deviated wells; simulate recovery mechanisms such as gas in solution, water thrust, gravity segregation and imbibition mechanisms.  KEYWORDS: Simulation, Naturally Fractured Reservoir, Permeability Tensor, Form Factor, NFR. RESUMENEl entendimiento del comportamiento de los yacimientos naturalmente fracturados (YNF) ha sido uno de los más grandes desafíos asumidos por varios investigadores a nivel mundial que trabajan en las áreas de caracterización, modelamiento y simulación de yacimientos. Debido al gran numero de YNFs a nivel mundial y consecuentemente la cantidad de aceite y gas contenidos dentro de ellos, estos yacimientos son un objetivo muy atractivo para la industria del petróleo. Sin embargo, debido al grado de complejidad involucrada en su modelamiento, se requiere una gran inversión en tiempo y dinero. La construcción de una herramienta de simulación numérica que tenga en cuenta el tensor de permeabilidad y el factor de forma dependiente del tiempo tiene un gran impacto cuando se desee modelar de manera más realista el desempeño de los YNF. SIMYNF es capaz de caracterizar la permeabilidad en tres dimensiones de sistemas fracturados y el flujo interporoso presente en el sistema matriz-fractura, basado en diferencias finitas para un yacimiento de aceite negro con doble porosidad y/o doble permeabilidad, de tres fases, tres dimensiones, flujo Darcy y condiciones isotérmicas. SIMYNF permite modelar pozos verticales, horizontales y desviados, simular mecanismos de recobro como gas en solución, empuje de agua, segregación gravitacional y mecanismos de imbibición Palabras Clave: Simulación, yacimientos